The peacebuilding process and the United Nations Security Council. A Theoretical Dialogue. - MOYA BARBA, Guillermo (Journal of the Spanish Institute for Strategic Studies, 2023)
The UN Security Council is the body responsible for the maintenance of international peace and security, and is the only body that can issue resolutions that are binding on UN Member States. In this article, we will analyse the role of this organ in the so-called "peacebuilding process", meaning post-war peacebuilding in so-called "failed" or "collapsed" states. To this end, we will use different authors whose works we will put in dialogue with each other in order to reach a final conclusion, including Rita Abrahamsen, Michael Ignatieff, and Zartman. From these authors, we will highlight some issues such as Ignatieff’s theory of the lesser evil, Zartman and Abrahamsen’s theory of necessity, greed and creed, or the integration of gender by the Spanish professor Itziar Ruíz-Giménez Arrieta. With this article we aim to study the peacebuilding process from a theoretical perspective and to bring into discussion, confrontation and harmony some of the main debates on how this process is seen from the outside and, specifically, how the Security Council has or has not been able to face this challenge.